The Impact of Financial Constraints on Companies’ Cash Holding and Firm Value: Evidence from Chinese Listed Companies - Li, Qing (2018)
Cash is the most important item for companies, which is a value creation factor and could reflect the value of firms, and financial constraints is an important issue to impact the cash holding behaviours and values of companies. In this paper, the cash holdingbehaviours and firm value of financial constrained and unconstrained companies wouldbe analysed separately, and there are four criteria will be used to measure financial constraints, which are debt rating, annual dividend payout ratio, firm size and the ownership of companies. The Chinese listed companies of A share for the period from 2010 to 2017 will be selected, and fixed random effect model will be applied. Based on this research, it could be concluded that financial constrained companies are more likely to reserve cash and could create more value for companies when holding every extra Chinese Yuan compared with unconstrained companies.